The General Systems Theory (GST) / Nur Zainie Abd Hamid - Abd Hamid, Nur Zainie (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
The General Systems Theory is developed by Ludwig von Bertalanffy, a biologist in 1928. This is an interdisciplinary theory that proposed a complex system shared several basic principles in order to function properly. At first, the theory is developed to describe the natural processes or nature of a complex system such as the human body functions. However, later, the theory has been applied to the business field. In the business field, the system theory is a framework to investigate and describe any group of objects that work together to produce some result. It focuses on the relations between the parts and connect them into a whole system. The GST also promises to offer a valuable concept for evaluating the human interrelation. In t he studies of perception, system theory is able to model human interactions that include intrapersonal, interpersonal and intergroup. It provides the basis for interpreting human experiences and the actual phenomenon